2020
DOI: 10.3390/ijerph17218076
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Young Korean Men’s Knowledge and Stigmatizing Attitudes about HIV Infection

Abstract: Stigma against people living with HIV (PLHIV) fosters depression and negatively impacts the quality of life in PLHIV and is a barrier to the whole process of treatment. This study aimed to identify the levels of knowledge and stigmatizing attitudes toward HIV infection among Korean men in their 20s and the factors influencing them. A cross-sectional design was used. Two hundred and eight Korean men in their 20s responded to self-report questionnaires that included items on knowledge and stigmatizing attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…According to multivariable analysis, we found that people aged 40-49 had lower discriminatory attitude toward PLWHA compared to younger (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) and older (50-59) age groups. This could be explained, as it was in the previous survey round [28], by the fact that people in this age group entered adolescence and young adulthood during Thailand's HIV epidemic in the early 1990s.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…According to multivariable analysis, we found that people aged 40-49 had lower discriminatory attitude toward PLWHA compared to younger (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) and older (50-59) age groups. This could be explained, as it was in the previous survey round [28], by the fact that people in this age group entered adolescence and young adulthood during Thailand's HIV epidemic in the early 1990s.…”
Section: Discussionmentioning
confidence: 92%
“…People living with HIV face enormous stigma and discrimination in society [26][27][28][29][30][31][32][33][34]. Poor HIV knowledge and awareness play a major role regarding the existence of stigma and discrimination associated with HIV/AIDS [34][35][36].…”
mentioning
confidence: 99%
“…Known-group validity was determined by comparing the HIV knowledge between participants based on four variables, namely education level, educational background, experience in attending a workshop about HIV and monthly expenses. Previous studies conducted in the Asian general population have demonstrated that different subgroups based on education levels [ 23 – 29 ], HIV education [ 28 ] and socioeconomic status [ 23 , 24 , 27 – 29 ] have different HIV knowledge levels. Therefore, the a priori hypothesis was made that participants with higher education level, educational background in health sciences, experience in attending a workshop about HIV and higher monthly expense had significant higher HIV knowledge than participants with lower education level, without educational background in health sciences, never experience in attending a workshop about HIV and lower monthly expense.…”
Section: Methodsmentioning
confidence: 99%
“…Korea is expected to show different results than other countries because of its Asian cultural characteristics emphasizing avoidance of family conflict (Yoshioka & Schustack, 2001) and a reluctance toward discussing sexual minorities or sexually transmitted infections beyond marital relationships. Further, since there are generally few opportunities in Korea to meet PLWH, it is easy to receive negative information about HIV through indirect channels (e.g., television, the Internet) and form negative attitudes (Shim & Kim, 2020). As HIV disclosure is influenced by contextual environments, such as family, community, and sociocultural norms (Eustace & Ilagan, 2010), it is necessary to study the disclosure status and related social network characteristics of Korean PLWH to provide effective counseling and interventions.…”
Section: Introductionmentioning
confidence: 99%